STRATEGI PAKISTAN MERESPON PERKEMBANGAN MILITER INDIA, 2015-2019 - Meylani Simarmata; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This paper will explain Pakistan's strategy to respond to India's military development by carrying out military development and military cooperation with a stronger country. Pakistan as a country that has always been in conflict with India since independence feels threatened by India's military development. Pakistan is developing its military in order to maintain the security of its country. This research uses neorealism perspective and security dilemma theory. The method used is descriptive qualitative research method. Meanwhile, data collection was carried out by means of library research consisting of books, journals, news and websites with reliable information This research proves that Pakistan has taken action in response to India's military development. Actions taken by Pakistan are the development of the domestic military, military cooperation with China and Russia in conducting military training and procurement of weapons.                                                                                                    Keywords: military cooperation, military development, security dilemma.